Study guides

☆☆

Q: How do you solve 9a squares - 100b squared?

Write your answer...

Submit

Still have questions?

Related questions

9a squared = 81a^2

9a- a number is squared when it is multiplied by itself, so 3a x 3a = 9a.

-21 = 9a - 15 - 3a -6 = 6a -1 = a

The difference of two squares (k2x2 - n2y2) is factorised as (kx+ny)(kx-ny). Therefore, 9a-64b2 is factorised as (3√a+8b)(3√a-8b).

9a + 4a = 26 13a = 26 a = 26/13 a = 2

4a - 2.1 = 9a + 5.4 4a - 9a = 5.4 +2.1 -5a = 7.5 -a = 1.5 a = -1.5

34

a= -0.8

4a2 - 9a + 5 = 4a2 - 4a -5a + 5 = 4a(a - 1) - 5(a - 1) = (4a - 5)(a - 1)

(a - 6)(2a + 3)

9a-a = 19+7a 8a = 19+7a 8a - 7a = 19 + 7a - 7a 1a = 19 a = 19

In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)

3a squared plus nine = 19a. 3a to the second power = 9a plus 9 = 19a.

9a-99 = -90

It is: 9a-a-a = 7a

It is the same as: 9a -4a = 5a

If: 9a = 18b Then: a = 2b

9a - 8a = a

9a verbal expression

9a+21 3(3a+7)

There is nothing you can do to 9a + 5 without knowing the value of a.

The simplified expression is -9a -9b.

2a+5a+9a = 16a

(9a + 2)(9a + 2)

That cannot be simplified any further so it is: 9a + 45z